The impact of forest thinning on the reliability of water supply in central Arizona. - Silvio Simonit; John P Connors; James Yoo; Ann Kinzig; Charles Perrings (PLoS ONE, 2015)
Economic growth in Central Arizona, as in other semiarid systems characterized by low and variable rainfall, has historically depended on the effectiveness of strategies to manage water supply risks. Traditionally, the management of supply risks includes three elements: hard infrastructures, landscape management within the watershed, and a supporting set of institutions of which water markets are frequently the most important. In this paper we model the interactions between these elements. A forest restoration initiative in Central Arizona (the Four Forest Restoration Initiative, or 4FRI) will result in thinning of ponderosa pine forests in the upper watershed, with potential implications for both sedimentation rates and water delivery to reservoirs. Specifically, we model the net effect of ponderosa pine forest thinning across the Salt and Verde River watersheds on the reliability and cost of water supply to the Phoenix metropolitan area. We conclude that the sediment impacts of forest thinning (up to 50% of canopy cover) are unlikely to compromise the reliability of the reservoir system while thinning has the potential to increase annual water supply by 8%. This represents an estimated net present value of surface water storage of $104 million, considering both water consumption and hydropower generation.